2017
DOI: 10.1175/jcli-d-16-0041.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Spatiotemporal Anomalies of Tibetan Plateau Snow Cover on Summer Precipitation in Eastern China

Abstract: Tibetan Plateau (TP) snow cover undergoes significant temporal and spatial variations during the winter and spring months. This study investigates the relationship between the spatiotemporal distribution of winter–spring snow cover (SC) over the TP and summer precipitation in eastern China (EC) using the singular value decomposition (SVD) method. Four simulation experiments are designed to validate the results of SVD analysis. Both observations and simulations show that heavier snow cover in the southern TP le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 65 publications
1
58
0
Order By: Relevance
“…The atmosphere component is the Community Atmosphere Model Version 4, and the land component is the Community Land Model Version 4 (CLM4). CESM has been widely used in other studies (e.g., Hurrell et al 2013) and can effectively simulate general circulation and climate characteristics over the TP and surrounding regions (Wang et al 2017). Studies have also suggested that CLM4 has good performance for land surface processes (Lawrence et al 2011) and can well describe soil moisture characteristics in FT processes .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The atmosphere component is the Community Atmosphere Model Version 4, and the land component is the Community Land Model Version 4 (CLM4). CESM has been widely used in other studies (e.g., Hurrell et al 2013) and can effectively simulate general circulation and climate characteristics over the TP and surrounding regions (Wang et al 2017). Studies have also suggested that CLM4 has good performance for land surface processes (Lawrence et al 2011) and can well describe soil moisture characteristics in FT processes .…”
Section: Methodsmentioning
confidence: 99%
“…Sea surface temperature anomalies as currently the most significant signal (e.g., the El Niño/La Niña phenomena) widely used for climate prediction (e.g., Ropelewski and Halpert 1987;Wang and Eltahir 1999;Wang et al 2000;Zhang et al 1999;Dai and Wigley 2000). Other factors such as soil moisture (e.g., Fischer et al 2007;Koster et al 2003Koster et al , 2004Seneviratne et al 2006;Conil et al 2007;May et al 2017;Ardilouze et al 2018) and snow cover/depth (e.g., Blanford 1884;Chen 1997;Wu and Qian 2003;Ding et al 2010;Wang et al 2017;Yang et al 2017;, have received much attentions. Studies suggested that sea surface temperature has a much smaller effect than soil moisture on predicting precipitation over mid-latitude land (Koster and Suarez 1995;Conil et al 2007;Yang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tibetan Plateau has a large snow cover area in the cold seasons (Pu et al, ; Z. Wang et al, ). Numerous studies have demonstrated impacts of the cold season Tibetan Plateau snow change on Indian and East Asian climate (e.g., Chen & Wu, ; Dey & Kumar, ; Ding et al, ; Fasullo, ; Hahn & Shukla, ; Kripalani et al, ; Ose, ; Si & Ding, ; C. Wang et al, ; Wu & Kirtman, ; Wu et al, ; Xiao & Duan, ; Zhang et al, ; Zhao et al, ; Zuo et al, ; Zhu et al, ). However, due to the lack of station observations at the high‐elevation region (You et al, ) and the small snow cover area in summer (Z. Wang et al, ), few studies have been conducted on the summer snow variations over the Tibetan Plateau and their impacts on the climate variability.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2017). Numerous studies have demonstrated impacts of the cold season Tibetan Plateau snow change on Indian and East Asian climate (e.g., Chen & Wu, 2000;Dey & Kumar, 1983;Ding et al, 2009;Fasullo, 2004;Hahn & Shukla, 1976;Kripalani et al, 2003;Ose, 1996;Si & Ding, 2013;C. Wang et al, 2017;Wu & Kirtman, 2007;Wu et al, 2010;Xiao & Duan, 2016;Zhang et al, 2004;Zhao et al, 2007;Zuo et al, 2012;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%